2015
DOI: 10.1158/2326-6066.cir-14-0211
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Receptor 2A Blockade Increases the Efficacy of Anti–PD-1 through Enhanced Antitumor T-cell Responses

Abstract: We have therefore revealed a potentially novel biomarker for the efficacy of anti-PD-1 that warrants further investigation in patients. Because our studies used SYN-115, a drug that has already undergone phase IIb testing in Parkinson disease, our findings have immediate translational relevance for patients with cancer.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
255
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 280 publications
(272 citation statements)
references
References 50 publications
9
255
0
Order By: Relevance
“…1 In our recent study, we identified CD73 as a potential biomarker for response to anti-PD-1. 2 Our finding that CD73 expression on tumor cells reduces the immune response evoked by anti-PD-1 mAb therapy, supports our previous findings that CD73 expression suppresses the immune response induced by anthracyclines 3 and the observations by Iannone et al that inhibition of CD73 enhanced the efficacy of anti-CTLA-4 in a melanoma model. 4 In humans, CD73 expression has been observed in several cancer types, driven by multiple factors in the tumor microenvironment including hypoxia, 5 and its expression is correlated with poor prognosis in triple negative breast cancer.…”
supporting
confidence: 92%
“…1 In our recent study, we identified CD73 as a potential biomarker for response to anti-PD-1. 2 Our finding that CD73 expression on tumor cells reduces the immune response evoked by anti-PD-1 mAb therapy, supports our previous findings that CD73 expression suppresses the immune response induced by anthracyclines 3 and the observations by Iannone et al that inhibition of CD73 enhanced the efficacy of anti-CTLA-4 in a melanoma model. 4 In humans, CD73 expression has been observed in several cancer types, driven by multiple factors in the tumor microenvironment including hypoxia, 5 and its expression is correlated with poor prognosis in triple negative breast cancer.…”
supporting
confidence: 92%
“…20,21,[32][33][34][35] These studies evidenced the CD39-CD73-adenosine receptor axis blockade as a promising therapeutic target. 31,[36][37][38][39][40][41][42] In line with these studies and with the objective to better understand the mechanism involved in the acquisition by TAM of an immunoregulatory phenotype, this study aimed at evaluating the impact of ATP and ATP metabolites on TAM functions.…”
Section: Introductionmentioning
confidence: 99%
“…41 Furthermore, an accumulation of extracellular adenosine in tumor microenvironment and the subsequent purinergic signaling are involved in the regulation of immune cell functions. 20,31,36,40 In this context, we hypothesized that the CD39-CD73-adenosine receptor axis plays a strategic role in the acquisition of immunoregulatory properties by tumor-infiltrating macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…6 Moreover, these studies demonstrated that blocking CD73 or A2A adenosine receptor significantly enhanced the antitumor activity of immunecheckpoint therapies. [7][8][9] In cancer patients, high levels of CD73 expression is increasingly reported to be associated with worse outcome in various types of cancers, including triple-negative breast cancer. Until recently, however, the prognostic value of CD73 in ovarian cancer, and in particular in HGSC, was unclear.…”
mentioning
confidence: 99%